2021
DOI: 10.2152/jmi.68.170
|View full text |Cite
|
Sign up to set email alerts
|

The new procedure for manual CPAP titration : the afternoon CPAP titration (aPT)

Abstract: Study Objectives : Although the full-night continuous positive airway pressure (CPAP) titration (fnPT) has been recognized as the gold standard for determining an optimal therapeutic pressure for obstructive sleep apnea (OSA) treatment, it is labor-intensive, time-consuming because it requires overnight polysomnography attended by well-experienced sleep technologists. The aim of this study is to develop a practical and feasible alternative titration method. Methods : We assessed demographic data and diagnostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…22,23 In contrast with the present study, the titration time was significantly shorter in some studies of afternoon or daytime titration group than night-time titration. 24 However, in those studies, outcomes including the residual AHI and CPAP compliance were similar between the two groups.…”
Section: Discussionmentioning
confidence: 88%
“…22,23 In contrast with the present study, the titration time was significantly shorter in some studies of afternoon or daytime titration group than night-time titration. 24 However, in those studies, outcomes including the residual AHI and CPAP compliance were similar between the two groups.…”
Section: Discussionmentioning
confidence: 88%
“…Recently, several studies, especially after the COVID-19 pandemic, assessed the efficacy of alternative titration modalities by comparing the standard method with the same alternative methods used in our study and reported near-similar results or compared it with other methods. 18,[21][22][23][24] Demographic and resource features of our region make it very difficult to use self-adjusting home therapeutic strategies as a calibration or therapeutic option.…”
Section: Discussionmentioning
confidence: 99%